Laser-induced atmospheric CuxO formation on copper surface with enhanced electrochemical performance for non-enzymatic glucose sensing. Issue 42 (8th September 2021) - Sedaghat, Sotoudeh; Nejati, Sina; Bermejo, Luis Helena; He, Zihao; Alcaraz, Alejandro M.; Roth, Alexander; Li, Zheng; Pol, Vilas G.; Wang, Haiyan; Rahimi, Rahim
Abstract : A tuneable laser-induced oxidation technique was demonstrated for the fabrication of binder-free and robust electroactive copper oxide film as a highly sensitive non-enzymatic glucose sensor. Abstract : Copper oxide nanostructures are widely used for various applications due to their unique optical and electrical properties. In this work, we demonstrate an atmospheric laser-induced oxidation technique for the fabrication of highly electrochemically active copper oxide hierarchical micro/nano structures on copper surfaces to achieve highly sensitive non-enzymatic glucose sensing performance. The effect of laser processing power on the composition, crystallinity, microstructure, wettability, and color of the laser-induced oxide on copper (LIO-Cu) surface was systematically studied using scanning electron microscopy (SEM), grazing incidence X-ray diffraction (GI-XRD), Raman spectroscopy, energy dispersive X-ray spectroscopy (EDX), EDX-mapping, water contact angle measurements, and optical microscopy. Results of these investigations showed a remarkable increase in copper oxide composition by increasing the laser processing power. The pore size distribution and surface area of the pristine and LIO-Cu sample estimated by N2 adsorption–desorption data showed a developed mesoporous LIO-Cu structure. The size of the generated nano-oxides, crystallinity, and electroactivity of the LIO-Cu were observed to be adjustable by the laser processing power. The electrocatalytic activity of LIO-Cu surfaces was studied by means of cyclic voltammetry (CV) within a potential window of −0.8 to +0.8 V and chronoamperometry in an applied optimized potential of +0.6 V, in 0.1 M NaOH solution and phosphate buffer solution (PBS), respectively. LIO-Cu surfaces with optimized laser processing powers exhibited a sensitivity of 6950 μA mM −1 cm −2 within a wide linear range from 0.01 to 5 mM, with exceptional specificity and response time (<3 seconds). The sensors also showed excellent response stability over a course of 50 days that was originated from the binder-free robust electroactive film fabricated directly onto the copper surface. The demonstrated one-step LIO processing onto commercial metal films, can potentially be applied for tuneable and scalable roll-to-roll fabrication of a wide range of high surface area metal oxide micro/nano structures for non-enzymatic biosensing and electrochemical applications.